(−)-Epicatechin gallate blocks the development of atherosclerosis by regulating oxidative stress in vivo and in vitro. Issue 18 (8th August 2021) - Yu, Jinjin; Li, Weifeng; Xiao, Xin; Huang, Qiuxia; Yu, Jiabao; Yang, Yajie; Han, Tengfei; Zhang, Dezhu; Niu, Xiaofeng
Abstract : ECG inhibits the development of atherosclerosis by inhibiting NF-κB and activating the Nrf2 signaling pathway to inhibit oxidative stress in vivo and in vitro . Abstract : (−)-Epicatechin gallate (ECG), as a compound in green tea extract polyphenols, has specific therapeutic effects against oxidative stress. Oxidative stress exists throughout the pathological development of atherosclerosis. In this study, two atherosclerosis models, oxidized low-density lipoprotein (ox-LDL)-induced vascular smooth muscle cells (VSMCs) and high fat diet (HFD)-induced ApoE −/− mice, were applied to explore the mechanism of ECG intervention on AS. In vivo and in vitro studies showed that ECG reduced the level of MDA and increased the activity of SOD, which are oxidative stress factors. ECG also improved HFD-induced disorder of lipid factor expression in the serum of ApoE −/− mice and alleviated oxidative stress by enhancing the antioxidant activity. The potential mechanism was supposed to be the inhibition of the phosphorylation of p65 by ECG in the NF-κB pathway in the aorta, thereby blocking the expression of inflammatory mediators. In addition, ECG increased the stability of atherosclerosis plaques by reducing the expression of MMP-2 and ICAM-1 in atherosclerosis diseased tissues. ECG reduced lipid accumulation in the aorta and its roots and also plaque neoplasia. Western blotting experiments indicated that ECG increased the nuclear transfer of Nrf2 and the expression of heme oxygenase 1 (HO-1) was increased. These results demonstrated that ECG significantly reduced the formation of aortic plaque in ApoE −/− mice which was possibly triggered by the inhibition of hyperlipidemia and oxidative stress that exhibited the anti-atherosclerotic potential.